Systematic variation in food web body-size structure linked to external subsidies - Perkins, Daniel M. (Biol Lett, 2021)
The relationship between body mass (M) and size class abundance (N) depicts patterns of community structure and energy flow through food webs. While the general assumption is that M and N scale linearly (on log–log axes), nonlinearity is regularly observed in natural systems, and is theorized to be driven by nonlinear scaling of trophic level (TL) with M resulting in the rapid transfer of energy to consumers in certain size classes. We tested this hypothesis with data from 31 stream food webs. We predicted that allochthonous subsidies higher in the web results in nonlinear M–TL relationships and systematic abundance peaks in macroinvertebrate and fish size classes (latter containing salmonids), that exploit terrestrial plant material and terrestrial invertebrates, respectively. Indeed, both M–N and M–TL significantly deviated from linear relationships and the observed curvature in M–TL scaling was inversely related to that observed in M–N relationships. Systemic peaks in M–N, and troughs in M–TL occurred in size classes dominated by generalist invertebrates, and brown trout. Our study reveals how allochthonous resources entering high in the web systematically shape community size structure and demonstrates the relevance of a generalized metabolic scaling model for understanding patterns of energy transfer in energetically ‘open’ food webs.